Ionic Conductivity of Hybrid Composite Solid Polymer Electrolytes of PEOnLiClO4-Cubic Li7La3Zr2O12 Films - Parisa Bashiri (MDPI AG, 2021)
Ionic conductivity of the polyethylene oxide-LiClO4 (PEOnLiClO4) solid polymer electrolyte (SPE) films with an EO:Li ratio (n) of 10, 12, 15, as well as the hybrid composite solid polymer electrolyte (CSPE) films of PEOnLiClO4 containing 50 wt% of cubic-Li7La3Zr2O12 (LLZO) sub-micron sized particles, have been studied by varying Li-salt content in the films. The complex AC dielectric permittivity and conductivity data obtained from electrical impedance measurements were fitted using a generalized power-law, including the effects of electrode polarization applied at low AC frequencies to obtain various relaxation times. In addition to increased mechanical and thermal robustness, the CSPE films show higher values of ionic conductivity, >10−4 S/cm at room temperature compared to those of SPE films with n = 12 and 15. On the contrary, the ionic conductivity of CSPE with n = 10 decreases by a factor of three compared to the corresponding SPE film due to increased polymer structural reorientation and Li-ion pairing effects. The Vogel–Tammann–Fulcher behavior of the temperature-dependent conductivity data indicates a close correlation between the ionic conductivity and polymer segmental relaxation. The PEO12LiClO4-LLZO film shows the lowest activation energy of ~0.05 eV.